Food preservatives influence biofilm formation, gene expression and small RNAs in Salmonella enterica. (November 2018) - Lamas, Alexandre; Paz-Mendez, Alba María; Regal, Patricia; Vazquez, Beatriz; Miranda, José Manuel; Cepeda, Alberto; Franco, Carlos Manuel
Abstract: Salmonella enterica is major foodborne pathogens. Salmonella persists in the food chain due to its ability to produce biofilms under different conditions. One of the biggest challenges in biofilm research is reproducing real food industry conditions. Also, food microbiologists have the challenge of elucidating the role of small RNAs (sRNAs) in the survival of foodborne pathogens in the food chain. This study evaluated food preservatives (sodium nitrite, sodium sulfite and sodium acetate-citric acid) effect on biofilm formation of ten S. enterica strains on two surfaces (polystyrene and stainless steel). The effects of preservatives on transcription of biofilm- and virulence-related genes and sRNAs were evaluated. All Salmonella strains produced biofilm in all the conditions evaluated. However, sodium sulfite reduced biofilm formation by Salmonella in both surfaces tested. Food preservatives influenced biofilm- and virulence-related genes and sRNAs transcription. This study highlights that Salmonella strains can produce biofilms in the presence of food preservatives, representing a public health problem. Fully understanding what metabolic pathways are modified by the presence of preservatives could allow developing new control strategies to prevent foodborne pathogens persistence in the food chain by using effective combinations of preservatives. Highlights: Food preservatives and surfaces highly influenced Salmonella biofilm formation. Sodium acetate reduced biofilm formation by Salmonella in stainless steel. Sodium nitrite had no effect in biofilm formation in Salmonella. Biofilm and virulence genes transcription were influenced by food preservatives. Small RNAs had an important role in biofilm formation regulation in Salmonella.